Penerapan Blended Learning Dalam Mereduksi Penggunaan Kertas (Studi Kasus Mata Kuliah Bahasa Rupa Di STSRD VISI) - Donna Carollina (LP2M Sekolah Tinggi Seni Rupa dan Desain Visi Indonesia (STSRD VISI), 2019)
Paper waste is the most produced waste in the field of education. No exception with the visual language courses held at STSRD VISI. In one semester, the visual language course requires a lot of paper use, where the paper is only used once. From these problems, visual language courses then apply the blended learning model whose method combines face-to-face and online methods using Google Classroom to deliver material and assignments. The results of implementing this blended learning model significantly reduce the number of paper used in visual language courses.